Asparagine Synthetase Chemotherapy - Richards, Nigel G. J. (2006)
Modern clinical treatments of childhood acute lymphoblastic leukemia (ALL) employ enzyme-based methods for depletion of blood asparagine in combination with standard chemotherapeutic agents. Significant side effects can arise in these protocols and, in many cases, patients develop drug-resistant forms of the disease that may be correlated with up-regulation of the enzyme glutamine-dependent asparagine synthetase (ASNS). Though the precise molecular mechanisms that result in the appearance of drug resistance are the subject of active study, potent ASNS inhibitors may have clinical utility in treating asparaginase-resistant forms of childhood ALL. This review provides an overview of recent developments in our understanding of (a) the structure and catalytic mechanism of ASNS, and (b) the role that ASNS may play in the onset of drug-resistant childhood ALL. In addition, the first successful, mechanism-based efforts to prepare and characterize nanomolar ASNS inhibitors are discussed, together with the implications of these studies for future efforts to develop useful drugs.